Indonesian humorous status in social media: An application of script-based semantic theory of humour - Sisila Fitriany Damanik; Mulyadi Mulyadi (Studies in English Language and Education, 2020)
This paper aims to analyse Indonesian humorous status in social media by applying the Script Semantic Theory of Humour (SSTH) and the parameters called Knowledge Resources (KRs) of the General Theory of Verbal Humour (GTVH). It is conducted by applying a qualitative method since the purpose of this study is primarily to describe and to establish the variation in a situation, phenomenon, problem, or event without quantifying them. The data is taken from Facebook, Twitter, and WhatsApp account followed by the first writer of this study for eight months. There are 17 statuses to be analysed, in which, seven statuses consist of 21 phrases analysed by applying SSTH theory, while the other 10 statuses consist of 14 phrases as set-up stages, 18 phrases, and three pictures as punchline stages analysed by applying GTVH theory. From the data being displayed, regarding the Superiority theory, it is found that people generally laugh because of other people’s misfortunes, and it emphasizes one’s superiority to the shortcomings of others. The people will laugh at individuals who are inferior or ugly, because they feel happy, and feel superior to them. Based on Release/Relief theory, humorous status also stems from regenerating something painful into something light-hearted. It is an indication of the misfortunate aspects of life. From the Incongruity theory, it is found that humour appears when there is an oddity between the concepts prepared in certain situations and the real events that are thought to be related to the concept. The paper further elaborates the findings and discuss them in detail.